Actualisation, complicité et complexité temporelles chez Habib Tengour - Djenane, Amina (Journal of Human Sciences, 2022)
In this scientific article, we have analysed the forms and the figures of temporal dualities in the two first books of the algerian author Habib Tengour: Le Vieux de la montagne and Sultan Galiév. The core of our research problem revolves around the temporal forms and figures through his premonitory writing which is retrospective and anticipatory at the same time. This work reveals an important aspect of Tangour’s literary writing embodied in the reinvention of the historical facts which takes, in his tale prose, an outstanding poetic form due to the spatiotemporal movements of his complex fictional plots.